A panel of 74 AISNPs: Improved ancestry inference within Eastern Asia. (July 2016) - Li, Cai-Xia; Pakstis, Andrew J.; Jiang, Li; Wei, Yi-Liang; Sun, Qi-Fan; Wu, Hong; Bulbul, Ozlem; Wang, Ping; Kang, Long-Li; Kidd, Judith R.; Kidd, Kenneth. K.
Highlights: A new 74 AISNP panel can distinguish 10 groups of population globally. Compared with 55-AISNPs, Southeast Asia and North Asia are newly assignable clusters. Likelihood ratio and ancestry components were analyzed for individual ancestry assignment. The new panel performed well on a test set of 500 individuals from 11 populations. Abstract: Many ancestry informative SNP (AISNP) panels have been published. Ancestry resolution in them varies from three to eight continental clusters of populations depending on the panel used. However, none of these panels differentiates well among East Asian populations. To meet this need, we have developed a 74 AISNP panel after analyzing a much larger number of SNPs for F st and allele frequency differences between two geographically close population groups within East Asia. The 74 AISNP panel can now distinguish at least 10 biogeographic groups of populations globally: Sub-Saharan Africa, North Africa, Europe, Southwest Asia, South Asia, North Asia, East Asia, Southeast Asia, Pacific and Americas. Compared with our previous 55-AISNP panel, Southeast Asia and North Asia are two newly assignable clusters. For individual ancestry assignment, the likelihood ratio and ancestry components were analyzed on a different set of 500 test individuals from 11 populations. All individuals from five of the test populations – Yoruba (YRI), European (CEU), Han Chinese in Henan (CHNH), Rondonian Surui (SUR) and Ticuna (TIC) – were assigned to their appropriate geographical regions unambiguously. For the other test populations, most of the individuals were assigned to their self-identified geographical regions with a certain degree of overlap with adjacent populations. These alternative ancestry components for each individual thus help give a clearer picture of the possible group origins of the individual. We have demonstrated that the new AISNP panel can achieve a deeper resolution of global ancestry.